2010
DOI: 10.3732/ajb.1000153
|View full text |Cite
|
Sign up to set email alerts
|

Development and characterization of polymorphic microsatellite markers in Momordica charantia (Cucurbitaceae)

Abstract: These markers will be useful to study population ecology and population differentiation among M. charantia species and its related species.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
32
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(34 citation statements)
references
References 6 publications
1
32
0
1
Order By: Relevance
“…Most SSRs developed by FIASCO (Wang et al, 2010) and from SSR-enriched fragments (Ji et al, 2012) showed motifs that were consistent with our results. Inconsistencies between our markers and those generated in previous studies may be owing to the differences among individual genomes.…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…Most SSRs developed by FIASCO (Wang et al, 2010) and from SSR-enriched fragments (Ji et al, 2012) showed motifs that were consistent with our results. Inconsistencies between our markers and those generated in previous studies may be owing to the differences among individual genomes.…”
Section: Discussionsupporting
confidence: 91%
“…The genome-based SSR development is far more than the efficiency of traditional methods, including FIASCO (Wang et al, 2010; Guo et al, 2012) and SSR-enriched fragments or libraries (Ji et al, 2012; Saxena et al, 2015). Most SSRs developed by FIASCO (Wang et al, 2010) and from SSR-enriched fragments (Ji et al, 2012) showed motifs that were consistent with our results.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In the present study, 9 out of 10 newly designed microsatellite markers also detected low level of heterozygosity (Ho = 0.00 to 0.20), except for Sed 01 (Ho = 0.85). Other genetic diversity studies on Cucurbitaceae using microsatellite markers demonstrated moderate to high heterozygosity (0.49 -0.75 [28], 0.26 -0.79 [29], 0.00 -1.00 [30], and 0.325 -0.867 [31]). Although individual species in the Cucurbitaceae family are generally cross-pollinated, chayote is known to be self-compatible [32] and a single plant of chayote shows a good fruit set and does not demonstrate clear inbreeding symptoms [33].…”
Section: Low Heterozygosity Detected In Chayote Collectionmentioning
confidence: 99%